Effects of prenatal substance exposure on infant temperament vary by context. (3rd June 2015) - Locke, Robin L.; Lagasse, Linda L.; Seifer, Ronald; Lester, Barry M.; Shankaran, Seetha; Bada, Henrietta S.; Bauer, Charles R.
Abstract: This was a prospective longitudinal multisite study of the effects of prenatal cocaine and/or opiate exposure on temperament in 4-month-olds of the Maternal Lifestyle Study ( N = 958: 366 cocaine exposed, 37 opiate exposed, 33 exposed to both drugs, 522 matched comparison). The study evaluated positivity and negativity during The Behavior Assessment of Infant Temperament (Garcia Coll et al., 1988). Parents rated temperament (Infant Behavior Questionnaire; Rothbart, 1981). Cocaine-exposed infants showed less positivity overall, mainly during activity and threshold items, more negativity during sociability items, and less negativity during irritability and threshold items. Latent profile analysis indicated individual temperament patterns were best described by three groups: low/moderate overall reactivity, high social negative reactivity, and high nonsocial negative reactivity . Infants with heavy cocaine exposure were more likely in high social negative reactivity profile, were less negative during threshold items, and required longer soothing intervention. Cocaine- and opiate-exposed infants scored lower on Infant Behavior Questionnaire smiling and laughter and duration of orienting scales. Opiate-exposed infants were rated as less respondent to soothing. By including a multitask measure of temperament we were able to show context-specific behavioral dysregulation in prenatally cocaine-exposed infants. The findings indicate flatter temperament may be specific to nonsocial contexts, whereas social interactions may be more distressing for cocaine-exposed infants.